2022
DOI: 10.3390/antiox11091830
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidases in Aortic Aneurysms

Abstract: Abdominal aortic aneurysms (AAAs) are a progressive dilation of the infrarenal aorta and are characterized by inflammatory cell infiltration, smooth muscle cell migration and proliferation, and degradation of the extracellular matrix. Oxidative stress and the production of reactive oxygen species (ROS) have been shown to play roles in inflammatory cell infiltration, and smooth muscle cell migration and apoptosis in AAAs. In this review, we discuss the principles of nicotinamide adenine dinucleotide phosphate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…Previous reports showed that ROS plays significant roles in promoting the pathogenesis of aortic aneurysms ( 60 62 ) via enhancing inflammatory cell infiltration, smooth muscle cell migration, and apoptosis in AAAs ( 63 ). We also reported that ROS in the ER, mitochondria, and other organelles ( 64 ) are interconnected in sensing metabolic stress ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that ROS plays significant roles in promoting the pathogenesis of aortic aneurysms ( 60 62 ) via enhancing inflammatory cell infiltration, smooth muscle cell migration, and apoptosis in AAAs ( 63 ). We also reported that ROS in the ER, mitochondria, and other organelles ( 64 ) are interconnected in sensing metabolic stress ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…This results in a perpetuating cycle of inflammation and oxidative stress, amplifying the vascular damage observed in AAA [ 21 ]. The upregulation of NADPH oxidases, responsible for ROS generation, signifies a pivotal event in this oxidative milieu, further underscoring the complexity of the molecular landscape [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological oxidative stress (OS) is defined as an imbalance between reactive oxygen species (ROS) and antioxidants, in favour of the former, leading to a disruption of redox signalling with consequence of oxidative damage to lipids, proteins and DNA. Increased activity of NAD(P)H oxidase, inflammation, over-expression of inducible nitric oxide synthase (iNOS), iron release from hemoglobin and endothelial dysfunction resulting in uncoupled endothelial nitric oxide synthase (eNOS) are recognized to be important sources of ROS production in AAA [ 10 , 11 ]. Therefore, reducing OS using antioxidants and especially dietary polyphenols could represent a potential strategy for limiting AAA development.…”
Section: Novel Therapeutic Options In Aaamentioning
confidence: 99%